RICCI FLOW EQUATION FOR STATIONARY AXISYMMETRIC METRIC - EDY KUSUMA (NIM 20206015), BENZ
Application of Ricci flow's ideas is used in general relativity theory. The study is taken for the special case, stationary axisymmetric metric which use Ricci flow equation. The result is compared to vacuum Einstein field equation, which give a conclusion that vacuum Einstein field equation is the trivial solution of Ricci flow equation. The other important discussion is integrability condition. Integrability condition in vacuum Einstein theory is satisfied but in Ricci flow that is not satisfied. Since Ricci Flow give bigger class of solutions which depend on geometry parameter itself compare with vacuum Einstein theory.